NEED ASSESSMENT DALAM PENDIDIKAN ISLAM: PERSPEKTIF KAUSAL UNTUK PERENCANAAN PENDIDIKAN YANG EFEKTIF - Nurul Masruni; Moch Isra Hajiri (CV. Lafadz Jaya, 2026)
Effective educational planning requires a comprehensive understanding of the evolving needs within the educational environment. In the context of Islamic education, these needs encompass not only academic aspects but also the spiritual, moral, social, and intellectual dimensions of learners. Therefore, need assessment serves as a vital tool for identifying the gap between the current situation and the desired ideal state. This article aims to examine the concept of need assessment in Islamic education, identify the factors causing the emergence of educational needs, and analyse the role of the causal approach in realising effective educational planning. This study employs a qualitative approach using library research. Data were obtained through a documentary study of various books, scientific articles, and relevant literature sources, and were subsequently analysed using content analysis. The results of the study indicate that educational needs in Islamic education are influenced by various internal and external factors, such as learner characteristics, teacher competence, institutional management, the social environment, educational policy, and technological developments. The causal analysis approach has proven capable of helping to identify the root causes of educational needs, thereby ensuring that the programmes designed are more targeted, efficient, and sustainable. Thus, the application of a causal-based need assessment can serve as an effective strategy for enhancing the quality of Islamic educational planning that is adaptable to changing times whilst remaining oriented towards the holistic achievement of Islamic educational objectives.